Entangling Text and Image in Sacred Space: Votive Mosaic Inscriptions from Gradište near Stojnik (Kosmaj, Serbia) - Špehar, Olga Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
On the site Gradište, near Stojnik on the mountain Kosmaj, the remains of a large complex were discovered. It consists of a longitudinal space divided into several units by transversal walls and a rotunda with an apse built into its eastern part. The architectural characteristics of the complex, as well as its overall appearance and dating to the middle of the 4th century, suggest that it was most probably used as a Christian sacred building. Floors covered in mosaics, although very fragmentarily preserved, also testify to this hypothesis. The largest preserved section of the mosaic consists of votive inscriptions intertwined with various geometrical and figural motifs. This paper is primarily dedicated to the research of those votive mosaic inscriptions, although the attention will also be paid to other represented motifs, in order to understand the iconography of the preserved part of the mosaic floor. The position of the mosaics, their votive character, and overall appearance suggest that they were intentionally placed in what was considered to be a liminal space between two parts of the complex, namely in the place that symbolically divided two spaces of various levels of sacrality. Therefore, this paper also examines other important questions in order to properly understand the meaning and importance of vota in the sacral space: who could see and read those inscriptions, how the inscriptions communicated to their ‘readers’, what kind of information they convey about the donors, etc.